A crise federativa e os usos dos espaços políticos na pandemia da Covid-19: um estudo a partir da feira de São Bento em Cascavel - CE - Lima, Victor Hugo Lemos (2024)
The COVID-19 pandemic exposed a federative crisis in which the lack of coordination in actions to combat the virus was evidenced by a disarticulation of powers between the Union, states and municipalities. This disarticulation was reproduced by speeches, decrees, social isolation policies and restrictions on economic activities, such as street markets. In this perspective, this research aims to analyse the relationship established between the federative crisis in the COVID-19 pandemic and the use of political spaces in the face of the situation of the fairgrounds of the São Bento fair in Cascavel. The research shows how the municipality dealt with the pandemic, political and federative crisis based on the analysis of the political spaces activated by different actors. The methodology was initially guided by bibliographic research focusing on the following theoretical axes: federative crisis, COVID-19 pandemic, political spaces and the São Bento Fair. The second stage was carried out based on documentary analyses such as municipal and state decrees, Minutes of the Cascavel City Council, Bills aimed at market vendors, and documents from the Northeast Consortium. Finally, fieldwork was carried out to conduct interviews with local leaders (politicians and market vendors). Among the results, it was possible to verify an alignment of actions between the Mayor of Cascavel and the Governor of the State of Ceará, in opposition to the proposals of the Federal Government, evidencing confusion about who held the power to relax and/or restrict economic activities. In view of these tensions, it was possible to identify and analyze that the mobilization of exclusive and open political spaces was anchored in agendas deliberated in the City Council and in demonstrations in the streets. The interviews also allowed to corroborate the active role of these political spaces in the demands of market vendors during the pandemic. In addition, it was possible to verify a new format for the São Bento fair and its transcendence to a place of political practice during the electoral period.